Competition between skin antimicrobial peptides and commensal bacteria in type 2 inflammation enables survival of S. aureus - Teruaki Nakatsuji; Samantha L. Brinton; Kellen J. Cavagnero; Alan M. O’Neill; Yang Chen; Tatsuya Dokoshi; Anna M. Butcher; Olive C. Osuoji; Faiza Shafiq; Josh L. Espinoza; Christopher L. Dupont; Tissa R. Hata; et al. (Cell Reports, 2023)
Summary: During inflammation, the skin deploys antimicrobial peptides (AMPs) yet during allergic inflammation it becomes more susceptible to Staphylococcus aureus. To understand this contradiction, single-cell sequencing of Il4ra−/− mice combined with skin microbiome analysis reveals that lower production of AMPs from interleukin-4 receptor α (IL-4Rα) activation selectively inhibits survival of antibiotic-producing strains of coagulase-negative Staphylococcus (CoNS). Diminished AMPs under conditions of T helper type 2 (Th2) inflammation enable expansion of CoNS strains without antibiotic activity and increase Staphylococcus aureus (S. aureus), recapitulating the microbiome on humans with atopic dermatitis. This response is rescued in Camp−/− mice or after topical steroids, since further inhibition of AMPs enables survival of antibiotic-producing CoNS strains. In conditions of Th17 inflammation, a higher expression of host AMPs is sufficient to directly inhibit S. aureus survival. These results show that antimicrobials produced by the host and commensal bacteria each act to control S. aureus on the skin.